Pelatihan Digital Marketing pada UMKM Widodo Aksesoris Desa Modalan Kecamatan Banguntapan Bantul - Nansi, Maria Regina; Raharjo, Suwanto; Rahayu, Suparni Setyowati; Astirin, Okid Parama (Journal of Dedicators Community, 2025)
The rapid development of digitalization has become an encouragement for MSMEs to further develop their business performance in the era of the 4.0 revolution. This Community Service focuses on the use of digital marketing in an effort to stimulate economic activities in Widodo Accessories Micro, Small and Medium Enterprises (MSMEs). Through this Community Service activity, it is hoped that partners will know the application of digital marketing and how digital marketing can affect the performance of Widodo Accessories MSMEs so that they can provide benefits both theoretically and practically. Online marketing has an impact on the company's performance and efficiency which is getting better, as evidenced by the 12% increase in sales along with the improvement in financial ratios. The positive impact after the digital marketing was implemented was the increase in sales and profits which also had a positive effect on the welfare of MSMEs. From this Community Service activity, it can be concluded that digital marketing slowly but surely plays an important role in improving the performance of MSMEs so that Widodo Accessories MSMEs must make digital marketing a tool to increase sales and profits